Türkiye’de İlgili Yönetmeliklere Uygun Isı, Su, Ses Ve Yangın Yalıtımı Çözümleri, Yalıtım Malzemeleri Ve Bir Bina Projesi Üzerinde Uygulama Örneği - Sözer, Nil (Fen Bilimleri Enstitüsü, 2015)
Bu çalışmada; ısı, su, ses ve yangın yalıtımları bütünleşik yaklaşımla ele alınmıştır. Öncelikle bu yalıtım çeşitleri ve uygulama metodları ile ilgili incelemeler yapılıp temel bilgiler verilmiştir. Türkiye’de bu konu kapsamına giren yönetmelik ve standartlar ile kullanılan yalıtım malzemeleri anlatılmıştır. Tüm inceleme ve tecrübelerin ışığında mevcut örnek bir bina projesi üzerinde yalıtım sistemleri çözümleri ve bunların maliyet analiz çalışmaları yapılmıştır. Bina için ısı, su ve ses yalıtım çözümleri önerilmiş, bunların yangına karşı dayanımı tahkik edilmiştir. Yalıtım projesi çözümlerinin TS 825 Isı Yalıtım Kurallarına göre hesapları ve maliyet analizleri sonuçları verilmiş, karşılaştırmalı analiz tablosunda yalıtımsız binaya göre enerji tasarrufu mukayesesi yapılıp yatırımların geri dönüş süreleri ortaya konmuştur. Elde edilen sonuçlar, öneriler ile birlikte sunulmuştur.

Heat, water, noise and fire insulations are taken into consideration in an integral manner within the content of this study. Above all, examinations in relation with these insulation types and application methods have been conducted, and the necessary basic information has been supplied. Afterwards, the regulations and standards being in force in Turkey and falling within the scope of this subject have been explained together with the insulation materials used. In the light of all examinations and experiences gained, a cost analysis study and applications of solutions with regards to insulation systems, has been carried out on an existing sample building, depending on the entire examinations performed. The calculations and cost analyses of insulation project solutions has also been conducted in accordance with the Heat Insulation Rules put forward through TS 825. Besides, an ‘energy saving’ comparison with a non-insulated building has been made via a comparative analysis table and the return period of the investments have been stated. The results that have been obtained are presented together with the related proposals.
Heat, Water, Noise And Fire Insulation Solutions In Turkey In Accordance With The Regarding Regulations, Insulation Materials And An Example Of Application On A Building Project
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2005
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2005
Keywords: Isı Yalıtımı; Su Yalıtımı; Ses Yalıtımı; Yangına Karşı Yalıtım; TS 825 Isı Yalıtım Hesabı; Yalıtım Projesi Çözümleri; Heat Insulation; Water Insulation; Noise Insulation; Insulation Against Fire; TS 825 Heat Insulation Calculation; Insulation Project Solutions